Platinum(II) oxalato complexes involving adenosine-based N-donor ligands: synthesis, characterization and cytotoxicity evaluation - Starha, Pavel; Popa, Igor; Trávníček, Zdeněk (Molecules (Basel, Switzerland), 2014)
A one-step synthetic procedure using the reaction of potassium bis(oxalato)platinate(II) with the corresponding N6-benzyladenosine derivative (nL) provided the [Pt(ox)(nL)₂]∙1.5H₂O oxalato (ox) complexes 1-5, involving the nL molecules as monodentate coordinated N-donor ligands. The complexes were thoroughly characterized by elemental analysis, multinuclear (¹H, ¹³C, ¹⁵N, 1¹⁹⁵Pt) and two dimensional NMR, infrared and Raman spectroscopy, and mass spectrometry, proving their composition and purity as well as coordination of nL through the N7 atom of the purine moiety. Geometry of [Pt(ox)(4FL)₂] (5) was optimized at the B3LYP/LANLTZ/6-311G** level of theory. The complexes were screened for their in vitro cytotoxicity against two human cancer cell lines (HOS osteosarcoma and MCF7 breast adenocarcinoma), but they did not show any effect up to the concentration of 50.0 µM (compounds 1, 2) or 20.0 µM (compounds 3-5).
Keywords: Adenosine; organoplatinové sloučeniny; Antineoplastic Agents; Molecular Structure; nádorové buněčné linie; lidé; molekulární struktura; oxaláty; protinádorové látky; ligandy; Ligands; Humans; adenosin; Oxalates; Organoplatinum Compounds; Cell Line, Tumor